Effects of hazelnuts and cocoa on vascular reactivity in healthy subjects: a randomised study - Adamo, Michela; Labate, Antonio Maria; Ferrulli, Anna; Macrì, Concetta; Terruzzi, Ileana; Luzi, Livio (International journal of food sciences and nutrition, 2018)
Cocoa helps maintain endothelium-dependent vasodilation; consumption of hazelnuts has been associated with reduced cardiovascular disease risk. This study assesses the effects of hazelnuts and cocoa on vascular reactivity and metabolic profile. Sixty-one healthy volunteers, examined in a randomised, controlled, two-week intervention, received one of six breakfast integrations containing either hazelnuts, cocoa, both or none. Consumption of unpeeled hazelnuts improved HDL-cholesterol (+7.3%, p = .01 vs. baseline, p = .02 vs. control). Brachial artery peak systolic velocities (PSV) at rest increased with hazelnut integrations by 43.4% (p = .04 vs. control) and hazelnut-cocoa integrations by 26.4% (p = .01 vs. control). PSV after 3-min cuff occlusion increased by 60.7% (p = .002 vs. control) with a peeled hazelnut snack and by 64.7% with a hazelnut-cocoa integration (p = .04 vs. control). The combination hazelnut-cocoa may act in a synergic and protective way on cardiovascular system.